Identifying the Motives of Instagram Users (Case Study: Psychology Students of Semnan University) - Rahman Marefat; maryam Saberi; mohammad agha dalavarpour; Safoura Arabian (International Journal of Information Science and Management, 2022)
The new media and technologies in the information era have affected all aspects of individuals in the information society. This research aimed to investigate the motivations for using Instagram as a social network among students of the Psychology and Educational Science Faculty of Semnan University. The present study was a survey in terms of methodology and applied research in terms of purpose. The research population comprised 442 students in the Faculty of Psychology and Educational Sciences at Semnan University. Totally, 205 individuals were selected through simple random sampling. Based on Gülnar, Balci and Çakir questionnaire (2010), a measure was provided for data gathering. To assess students' motives in using Instagram as a social network, exploratory factor analysis, one-sample t-test, and description analysis were used, and the collected data were analyzed using SPSS software (version 24). Findings showed that six factors of narcissism and self-expression, passing the time and entertainment, curiosity about events and memories, information seeking, creating social and emotional capital, and relationship maintenance were the most important motivations for students to use Instagram as a social network. The results further showed that three factors (i.e. information seeking, passing time, and relationship maintenance) were suggested as the three main motivations of students. Psychology students of Semnan University use social networks such as Instagram according to real-life conditions to compensate for their shortcomings and deficiencies and meet their needs. https://dorl.net/dor/20.1001.1.20088302.2022.20.4.15.4